HYPERTENSION: A SUFFIECIENT RISK FACTOR FOR CARDIOVASCULAR DISEASES - Khan, Subhana Akber; Pervaiz, Farrah; Afridi, Saleha; Babar, Ayesha; Hafeez, Assad (Pakistan Armed Forces Medical Journal, 2021)
Hypertension is a risk factor that can cause hypertension leading to cardiovascular diseases. A high or persistent blood pressure level of 140/90mmHg is known as hypertension which is divided into further stages. Blood pressure is the pushing force with which the heart pumps blood against the walls of arteries. High blood pressure is a serious medical condition in which the force of blood against wall of an artery is elevated than the normal which is called as hypertension. Recent guidelines of ICD-11 categorizes blood pressure into four levels. In a clinical setting, an average of blood pressure measurements is usually taken by healthcare providers. These categories are labeled as normal blood pressure, elevated blood pressure, stage 1 hypertension and stage 2 hypertension according the blood pressure measurements. Hypertension is associated with cardiovascular diseases which results in significant morbidity and mortality. Hypertension for a long-term or chronic elevation of blood pressure causes organ damage, eventually. It can be divided into primary or essential hypertension which occurs in 95% of cases whereas; secondary hypertension occurs in 5% of the cases. There are several possible and interrelated factors that are involved in development of hypertension. Intake of sodium in diet, insulin resistance, genetics, and obesity are some of the non-modifiable risk factors for hypertension. Whereas; renin-angiotensin-aldosterone system, cardiac output, peripheral resistance are also implicated in hypertension development. It is a wide known considered risk factor not only for cardiovascular diseases but for renal diseases as well. In this review article.....